Translanguaging in a Context of Colonized Education: The Case of EFL Classrooms for Arabic Speakers in Israel. (11th May 2022) - Awayed-Bishara, Muzna; Netz, Hadar; Milani, Tommaso
Abstract: Previous studies of translanguaging in educational contexts indicate that translanguaging practices have the potential to generate a decolonial, emancipatory process for language-minoritized students. However, these insights are mainly based on studies of minoritized learners of English as a second language. Drawing on a one-year ethnographic study conducted in six Palestinian schools in Northern Israel, the present study investigated the effects of translanguaging in a conflict-ridden context, where both the teachers and the learners are minoritized and English is learned as a foreign language. Drawing upon Butler's (1997) concept of implicit censorship and Stroud's (2018) linguistic citizenship, we propose colonized education as a framework for understanding the tensions between translanguaging, as a decolonial pedagogy, and English language learning. Our findings suggest that while translanguaging may indeed have a liberatory force, it could also, at the same time, take an emotional-pedagogic toll that may hinder language learning rather than support it. In contrast, critical discussions of issues that are politically and emotionally laden may be highly effective, even when conducted in the target language.